IMPLIKASI STRATEGI PEMASARAN MELALUI KOMODIFIKASI AGAMA DI INDONESIA - Yustati, Herlina (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Religion in Indonesia is divided into Muslim, Christian, Catholic, Hindu, Buddhist, Khong Hu Chu and Other Religions. Religion Islam is the majority religion embraced by the Indonesian population, so that business people use this opportunity to re-commodification of religion. Commodification describes how capitalism launched an aim to accumulate capital, or realize the transformation of use-value into exchange value. The commodification of Islam in Indonesia occurred in various aspects. Mislanya commodification "sharia" through aspects of banking, insurance, hotel, tourism, etc. The commodification of Islamic symbols such as headscarves and halal labeling. Besides being able to be used as a marketing strategy for businesses, komodiikasi Islam also bring positive things if businesses make this situation as a means of education. The impact of the commodification of Islam such as the increasing development of Islamic financial institutions in Indonesia, increased public awareness to abandon usury, increased public awareness using the "sharia", the increasing number of Muslim women who wear the hijab and the increasing awareness of Muslims to use halal products not only in food but also in cosmetics.